A fotografia como recurso didático no processo de ensino de química - (:unkn) unknown (Universidade Federal do Pampa, 2022)
In the first half of the 19th century, the photographic record was presented to the French Society of Sciences and, from that moment on, photography permeated the sciences in its most diverse areas and with its expansion, the lack of tools for such an apparatus became evident. for some research. As soon as, its evolution occurred in the most diverse levels, and with that, it surpassed the academic walls, registering the society, the daily one and transforming it into something indispensable in the 21st century. The present work aims to investigate the use of photography as a tool in the teaching-learning process of chemistry, seeking to contribute to the expansion of scientific concepts through observational writing, using the daily life of students as an object of study. It is understood that in the current scenario, photography is linked beyond digital cameras, including itself as one of the main tools of cellular devices, in this way, it is questioned how such a globalized and easily accessible instrument is little used to the education. Knowing that it contains a great potential for observation and discussion in the school space and in different areas of knowledge. The research was carried out with 12 students from a third-year high school class of a public school located in Aceguá/RS, initially applying field research and soon after implementing a didactic sequence that was developed in six moments (asynchronous, synchronous and face-to-face), which are all presented and discussed in the course of the work and evaluated qualitatively. It is considered that the research corresponded to the expected results, with a positive impact on the construction of students' knowledge, thus expanding scientific concepts and improving students' creativity, autonomy and observation of the chemistry present in their daily lives.
Keywords: Fotografia; Química; Ensino; Recurso didático; Photography; Chemistry; Teaching; Didactic Resource; CNPQ::CIENCIAS EXATAS E DA TERRA